Chemotherapy beyond immune checkpoint inhibitors in patients with metastatic colorectal cancer. (September 2020) - Martin-Romano, Patricia; Ammari, Samy; El-Dakdoukti, Yolla; Baldini, Capucine; Varga, Andreea; Vuagnat, Perrine; Angevin, Eric; Bahleda, Rastislav; Gazzah, Anas; Champiat, Stephane; Michot, Jean M.; Postel-Vinay, Sophie; et al.
Abstract: Background: Immune checkpoint inhibitors (ICIs) alone or in combination with chemotherapy (CT) are the current standard of therapy in several cancer types. Patients (pts) with lung cancer display higher response rates to CT when given after ICIs. Although ICIs have failed to demonstrate antitumour activity in microsatellite stable (MSS) metastatic colorectal cancer (mCRC), little is known about CT effect after ICIs. We aimed to assess whether sequential ICIs followed by CT may be an alternative therapeutic approach in a population of pts with mCRC. Material and methods: We retrospectively assessed CT after ICI (CAICI) failure in pts with mCRC. The ICI regimen consisted of anti-PD(L)1 alone or in combination. The primary end-point was objective response rate. Progression-free survival (PFS) and overall survival (OS) were secondary end-points. Results: Between 2014 and 2018, 29 pts with mCRC received CAICI (MSS tumours, 27 pts [86%]). The median number of previous lines was 4 (range, 2–7). Regimens included TAS-102 (n = 14), FOLFIRI (irinotecan, leucovorin, and fluorouracil; n = 6) or FOLFOX (oxaliplatin, leucovorin, and fluorouracil; n = 4), regorafenib (n = 3) and carboplatin (1 pt with BRCA mutation). Partial response and stable disease were observed in 4 (19%) and 9 (43%) pts, respectively (disease control rate, 62%). The median PFS and OS were 3.8 months (95% confidence interval [CI] = 1.5–5.4) and 8.0 months (95% CI = 4.2–14.0), respectively. Conclusion: ICIs administered before CT might enhance cytotoxic effects even in pts with immunorefractory MSS mCRC. The results of this small cohort need to be validated in independent prospective cohorts. The role of ICIs as modifiers of both tumour cells and microenvironment in mCRC deserves further research. Highlights: Chemotherapy (CT) beyond immunotherapy was assessed in patients with metastatic colorectal cancer (mCRC). Immunotherapy followed by CT provides tumour control in mCRC. Immunorefractory mCRC could benefit from sequential immunotherapy and CT. Immunotherapy-induced delayed effects might enhance chemotherapy in mCRC.